Staphylococcus sp e enterobactérias isoladas de mastite recorrente em oito rebanhos da região de Uberlândia-MG : perfil de suscetibilidade aos antimicrobianos - Santos, Cristiane Diniz Matoso (2006)
About 134 milk samples proceeding from cows with clinical or subclinical recurrent mastitis in eight properties of Uberlândia-MG were submitted the microbiological analysis. The samples had been submitted the culture to verify the presence of Staphylococcus sp and enterobacterias and isolated specimens were submitted the different tests to verify the susceptibility to the antimicrobials. Additionally, the enterobactérias and Staphylococcus sp isolated had been identified to the species level. The mastitic milk samples were evaluated and demonstrated bacterial growth in 61,19% (82/134) occasions. The more prevalent etiologic agent was the Staphylococcus sp, (90,24% - 74/82) followed of the enterobacterias (24,39% - 20/82). The susceptibility test by disk diffusion demonstrated that the majority staphylococci strains of the isolated presented multiresistance. Of 38 Staphylococcus specimens had presented resistance to the oxacillin (40,54% - 30/74), in thirty this isolated the resistance was confirmed by the CMI (40,54% - 30/74) and twenty-five the mec A gene was detected (33,78% -25/74). The antibiogram for the enterobacterias demonstrated that (20/20) they had 100% presented resistance to the ampicillin and amikacin, amoxacillin and tetracycline (65.00% - 13/20), ceftazidime and chloramphenicol (15.00%-3/20), cefotaxime(10.00%-2/20), aztreonam and gentamicine (5.00%-1/20)and ceftriaxone, imipinem and ciprofloxacin (0% -0 /20). Only isolated (5%) identified as Escherichia coli demonstrated resistance to the ceftazidime and demonstrated to be producing of ESBL by double-disk diffusion test. The results had evidenced high resistant between the strains isolated, strengthening the importance of the adequate and monitored use of antibiotics, since these microrganisms can be spread by milk and transform into serious problem of public health.